Structure and dynamics of the platelet integrin-binding C4 domain of von Willebrand factor - Xu, Emma-Ruoqi; Bülow, Sören von; Aponte-Santamaria, Camilo; Simon, Bernd; Gräter, Frauke; Hennig, Janosch (Blood, 2019)
Von Willebrand factor (VWF) is a key player in the regulation of hemostasis by promoting recruitment of platelets to sites of vascular injury. An array of 6 C domains forms the dimeric C-terminal VWF stem. Upon shear force activation, the stem adopts an open conformation allowing the adhesion of VWF to platelets and the vessel wall. To understand the underlying molecular mechanism and associated functional perturbations in disease-related variants, knowledge of high-resolution structures and dynamics of C domains is of paramount interest. Here, we present the solution structure of the VWF C4 domain, which binds to the platelet integrin and is therefore crucial for the VWF function.